Brill's companion to ancient Greek scholarship - Montanari, Franco; Matthaios, Stephanos; Rengakos, Antonios (Brill's companions in classical studies., 2015)
Brill's Companion to Ancient Scholarship aims at providing a reference work in the field of ancient Greek and Byzantine scholarship and grammar, thus encompassing the broad and multifaceted philological and linguistic research activity during the entire Greek Antiquity and the Middle Ages. The first part of the volume offers a thorough historical overview of ancient scholarship, which covers the period from its very beginnings to the Byzantine era. The second part focuses on the disciplinary profile of ancient scholarship by investigating its main scientific topics. The third and final part presents the particular work of ancient scholars in various philological and linguistic matters, and also examines the place of scholarship and grammar from an interdisciplinary point of view, especially from their interrelation with rhetoric, philosophy, medicine and nature sciences.